Penyulingan Daun Temurui (Murraya Koenigii) dengan Metode Distilasi Uap sebagai Salah Satu Cara Meningkatkan Nilai Ekonomis - Raju Pamungkas; Adriana Adriana; Muhammad Yunus (Politeknik Negeri Lhokseumawe, 2022)
Temurui leaves or curry leaves (Murraya Koenigii) are widely available in Aceh, this plant is one of the wild plants, but unfortunately it is only used as a cooking spice by the community. In this study, the temurui leaves were distilled to extract the essential oil, thereby increasing the economic value of the temurui leaves. The tests carried out to determine the criteria for the essential oil of temurui leaves (curry leaves) were yield, density, refractive index and GC-MS analysis. The temurui leaf distillation is operated by the steam boiler distillation method and uses leaves that have been aerated, using variations in drying 0, 1, 2, and 3 days and distillation time variations of 4, 5, 6, and 7 hours, with a distillation time of 7 hours. hours and 1 day of drying to get the best yield and distillate with a value of 21.5 ml. Based on the research conducted, it can be concluded that the longer drying time can affect the yield obtained, and the longer the refining time, the more oil distillate is obtained. The results of GC-MS obtained Caryophyllene of 76.33% which has a function as an antibacterial, and -Humulene 18.49% which has a function as a prevention of cancer cell growth, with the highest density of 0.8928 and the result of a refractive index of 1.5128. it has fulfilled the SNI for teumuri leaf essential oil. Keywords: Murraya Koenigii, Temurui Leaves, Distillation, Curry Leaves.